Analyzing the spatio-temporal patterns and impacts of large-scale data production events in OpenStreetMap - Grinberger, A. Yair; Schott, Moritz; Raifer, Martin; Troilo, Rafael; Zipf, Alexander (Zenodo, 2019)
Grinberger et al. (2019). Analyzing the spatio-temporal patterns and impacts of large-scale data production events in OpenStreetMap - - - In: Minghini, M., Grinberger, A.Y., Juhász, L., Yeboah, G., Mooney, P. (Eds.). Proceedings of the Academic Track at the State of the Map 2019, 9-10. Heidelberg, Germany, September 21-23, 2019. Available at https://zenodo.org/communities/sotm-2019  - - - DOI: 10.5281/zenodo.3387671
Gesehen am 19.02.2026
Aus: Minghini, M., Grinberger, A.Y., Juhász, L., Yeboah, G., Mooney, P. (Eds.). Proceedings of the Academic Track at the State of the Map 2019, 9-10. Heidelberg, Germany, September 21-23, 2019. Available at https://zenodo.org/communities/sotm-2019